The function of moral rules in Islamic legal theory - taha merghati; shaban haghparast; mahdi shakeri (اخلاق وحیانی, 2022)
The following article seeks to answer two basic questions. First, what is the relationship between law and ethics? Although the principle of the relationship between these two important social areas seems clear, the quality of the relationship between the two is not clear. The relationship between ethics and law has long been a point of contention between moral philosophers and jurists. The reason for this difference is the difference between the different schools of law and ethics. In the Islamic view, the origin of both the field of ethics and law goes back to the will of the shari'a, and therefore the moral school of Islam will find a different relationship with law than other moral schools. The second question is how ethics as a different and at the same time law-related field can influence the legislative process? Can the legislature enforce the rule of law on moral judgments that naturally lack legal guarantees? Referring to the works of jurists in the field of authority of the Islamic ruler, it seems that if we are based on the theory of expediency of Imam (ra), the legislator can establish any expediency approved by experts as law, so moral rules if the interest of society requires. They will have the power to become law.